Tough elastomer hybrid hydrogel and preparation method thereof
Through the one-pot synthesis strategy, the emulsion system and surfactant were used to synchronize the construction of elastomer and hydrogel networks, which solved the problem of uneven interface stress distribution of existing composite materials, and achieved efficient integration and excellent mechanical properties of strong elastomer hybrid hydrogels.
Patent Information
- Application Number
- CN202510094782.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The stress distribution of existing elastomer-hydrogel composites in the interface area is uneven, and they are prone to cracks or interface failure, affecting the overall performance and long-term stability.
A one-pot synthesis strategy is adopted to mix the hydrogel prepolymerization liquid and the elastomeric prepolymerization liquid through the emulsion system, use surfactant to form a stable emulsion, and trigger free radical polymerization through light or thermal stimulation, and synchronously build the elastomer and hydrogel network to form strong covalent bonds to enhance interface binding force.
It realizes efficient integration of elastomers and hydrogels. The hybrid materials inherit the mechanical strength of the elastomers and integrate the biocompatibility and multifunctional characteristics of the hydrogels, excellent mechanical properties, and good biosafety.
Smart Images

Figure CN119899309A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogel materials, and in particular to a strong and tough elastomer hybrid hydrogel and a preparation method thereof. Background Art
[0002] Soft materials, especially elastomers and hydrogels, have become the core components driving the development of modern technology and are widely used in the fields of tissue engineering, drug delivery, biomedical devices, microfluidics, optics, and soft robotics. Elastomers play an important role in many applications that require both flexibility and strength due to their excellent mechanical strength, elasticity, and durability. Hydrogels, with their good biocompatibility, low immunoreactivity, and softness, have become ideal materials in the biomedical field, especially for contact with biological tissues or implantation applications. The advantages of elastomers and hydrogels complement each other. Therefore, the organic integration of the two into a new hybrid material that combines the advantages of both has broad application prospects.
[0003] Combining the excellent mechanical properties of elastomers with the excellent biocompatibility of hydrogels provides a new strategy for designing new soft materials. However, the differences in physical and chemical properties between hydrophilic hydrogels and hydrophobic elastomers, especially in terms of interfacial compatibility and performance matching, make the seamless integration of the two extremely challenging. Currently, most elastomer-hydrogel composites rely on a layered structure, that is, the hydrogel is adhered to the surface of the elastomer substrate. This design scheme relies on complex surface engineering techniques to ensure a sufficiently strong interfacial bonding force between the hydrogel and the elastomer. Specifically, the preparation of the composite usually requires surface modification of the substrate to enhance the interaction between the two materials and improve the interfacial strength. Nevertheless, due to the significant difference in mechanical strength between hydrogels and elastomers, the stress distribution in the interface region between the two is uneven, which is prone to cracks or interfacial failure, seriously affecting the overall performance and long-term stability of the composite. Especially under external load or deformation conditions, this stress concentration problem is more obvious, thus limiting the effectiveness of elastomer-hydrogel composites in certain high-load applications.
[0004] At present, there are relatively few studies on macroscopically homogeneous elastomer-hydrogel composites. Huang et al. modified the pre-synthesized elastomer microspheres by γ-ray irradiation technology, so that they acted as both initiators and cross-linkers during the composite process, thereby successfully achieving the grafting of hydrophilic chains. Recently, Tian et al. reported a new method that uses γ-rays to penetrate hydrophilic monomers into the hydrophobic network of elastomers and convert elastomers into hydrogels. Although these methods have made positive progress to a certain extent, their processes are complex and involve multiple operating steps, including pre-synthesis of elastomers, chemical modification, and interface functionalization, and often require the use of expensive equipment.
[0005] Therefore, with the growing demand for materials that have both the mechanical strength of elastomers and the biocompatibility and functionality of hydrogels, the development of efficient and simple integration strategies and preparation methods has become the key to current research. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems and provide a strong elastomer hybrid hydrogel and a preparation method thereof. The hydrogel prepared by the method has excellent mechanical properties and good biosafety.
[0007] The technical scheme adopted by the present invention is as follows: a strong and tough elastomer hybrid hydrogel, comprising the following raw material components: an initiator, an elastomer monomer, an elastomer crosslinking agent, a water-soluble monomer, a water-soluble crosslinking agent, a surfactant, and water; the elastomer monomer is 1-90% of the total volume of the raw material components, the elastomer crosslinking agent is 0-100 mol% of the elastomer monomer; the water-soluble crosslinking agent is 0-20 mol% of the water-soluble monomer.
[0008] Preferably, the initiator is 0.01-1 mol% of the elastomer monomer; the ratio of the mass of the water-soluble monomer to the volume of water is 1:2; the volume ratio of the elastomer monomer to water is 0.25-4:2; and the volume ratio of the surfactant to water is 0.05-0.1:1.
[0009] Preferably, the raw material components further include agar, and the concentration of agar in the raw material components is 10-50 mg / mL.
[0010] Preferably, the initiator is a free radical polymerization thermal initiator or a photoinitiator; the thermal initiator is one of dibenzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), potassium persulfate (KPS), and ammonium persulfate (APS); the photoinitiator is one of 1-hydroxycyclohexyl phenyl ketone, phenyl dimethoxyacetophenone, photoinitiator 2959, A-ketoglutaric acid, photoinitiator LAP, photoinitiator 819, photoinitiator TPO, and benzophenone (BP).
[0011] Preferably, the elastomer monomer is one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-phenylethyl acrylate, isooctyl methacrylate, n-octyl acrylate, isooctyl acrylate, diethylaminoethyl methacrylate, vinyl propionate, methyl methacrylate, butyl methacrylate, hexyl methacrylate, and vinyl acetate.
[0012] Preferably, the elastomer crosslinking agent is one of ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,12-dodecanediol dimethacrylate, 1,13-tridecanediol dimethacrylate, p-vinylbenzene, and spiropyran.
[0013] Preferably, the water-soluble monomer is one of acrylamide, methacrylamide, N-(2-hydroxyethyl)acrylamide, N,N-dimethylacrylamide, N-acryloylglycinamide, acrylic acid, N-isopropylacrylamide, and hydroxyethyl methacrylate; and the water-soluble crosslinking agent is one of N,N'-methylenebisacrylamide, polyethylene glycol 600 diacrylate, and polyethylene glycol 1000 diacrylate.
[0014] More preferably, the surfactant is one of Tween 20, Tween 60, Tween 80, PVP, Span, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.
[0015] More preferably, the hydrogel has a tensile strength of 0.1 MPa-3.3 MPa, an elongation at break of 3.2-22.5, and an elastic modulus of 0.2 MPa-1.9 MPa.
[0016] The present invention also provides a method for preparing the above-mentioned tough elastomer hybrid hydrogel, comprising the following steps:
[0017] S1, mixing an initiator, an elastomer crosslinking agent and an elastomer monomer uniformly to prepare a solution A;
[0018] S2, uniformly mixing a water-soluble monomer, a water-soluble crosslinking agent and an aqueous solution containing a surfactant to obtain a solution B;
[0019] S3. Evenly mix solution A in S1 and solution B in S2 at a volume ratio of 0-1.3:1, inject into a mold, initiate polymerization, and obtain a strong elastomer hybrid hydrogel.
[0020] The beneficial effects of the present invention are:
[0021] 1) The present invention proposes a general and efficient one-pot synthesis strategy for preparing tough elastomer cross-linked hybrid hydrogels. The method utilizes an emulsion system, an aqueous phase composed of a hydrogel prepolymer and an oil phase composed of an elastomer prepolymer, to form a stable water-in-oil emulsion under the action of a surfactant, and then utilizes external light or heat stimulation to initiate free radical polymerization of the elastomer and the hydrogel, thereby simultaneously constructing an elastomer and hydrogel network. And the interfacial copolymerization of the two is utilized to form a strong covalent bond between the two components, ensuring the overall homogeneity and stability of the hybrid material. Through this one-pot method, the elastomer and the hydrogel are efficiently integrated, and the hybrid material not only inherits the excellent mechanical strength of the elastomer, but also integrates the good biocompatibility and multifunctional properties of the hydrogel.
[0022] 2) The hydrogel prepared by the present invention has excellent mechanical properties, specifically: tensile strength ranges from 0.1MPa to 3.3MPa, elongation at break ranges from 3.2 to 22.5, elastic modulus ranges from 0.2MPa to 1.9MPa, and toughness ranges from 0.5 to 15.0MJ / m 3 , high compression strength, adjustable range 17.9MPa-50.7MPa.
[0023] 3) The transparency of the hydrogel prepared by the present invention can be adjusted. The transparency of the hydrogel can be affected by adjusting the amount of the elastomer crosslinker used (0% to 100 mol%, relative to the molar ratio of the elastomer monomer) and the elastomer ratio. The change in the content of the elastomer crosslinker affects the crosslinking degree of the hydrogel, thereby affecting the scattering and transmission characteristics of light, and achieving a smooth transition between transparent and opaque states; at the same time, by adjusting the proportion of the elastomer monomer (1% to 90%), the transparency and structural characteristics of the hydrogel can be further optimized. The change in the elastomer ratio has an important influence on the macroscopic morphology and microstructure of the hydrogel, so that the transparency of the hydrogel can be finely adjusted between transparent and opaque.
[0024] 4) The hybrid hydrogel prepared by the present invention has the advantages of both the temperature responsiveness of elastomers and the good biocompatibility of hydrogels, and can be widely used in the fields of biomedicine, sensors, soft robots, etc.
[0025] 5) The preparation method of the present invention is simple, easy to operate, and suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are hydrogels of different shapes prepared by using molds in Example 1.
[0027] Figure 2 The circular hydrogel sheets prepared in Example 1 using different elastomer ratios.
[0028] Figure 3The circular hydrogel sheets prepared in Example 2 using different elastomer cross-linking agent contents.
[0029] Figure 4 The stress-strain comparison diagram of the hybrid hydrogels containing different elastomer ratios and the hydrogel control sample without elastomer in Example 1 is shown in FIG.
[0030] Figure 5 is the compressive stress-strain diagram of the hybrid hydrogel in Example 1.
[0031] Figure 6 This is a diagram of the temperature-responsive mechanical properties of the hybrid hydrogel in Example 1.
[0032] Figure 7 These are the cell live-dead staining results and cell survival rate of the hybrid hydrogel in Example 1. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0034] Example 1
[0035] The hybrid hydrogels were prepared by the following steps (the hydrogels with different elastomer ratios were prepared in this example):
[0036] (1) 10 mg of photoinitiator 819, 10 μL of elastomer crosslinker 1,6-hexanediol dimethacrylate and 1 ml of elastomer monomer methyl acrylate were mixed to prepare solution A;
[0037] (2) 1 g of acrylamide and 2 mL of 1 vol% Tween 80 aqueous solution were manually shaken and mixed to obtain solution B;
[0038] (3) Solution A was mixed with solution B at 25 vol% of the total volume of solution A and solution B, vortexed for 5 min using a vortex disperser, and then injected into a glass mold with a 1 mm thick Teflon gasket using a syringe. After irradiation for more than 3 minutes, a hybrid hydrogel with an elastomer ratio of 25 vol% was obtained.
[0039] According to the above preparation method, solution A was mixed with solution B at 8 vol%, 14 vol%, 40 vol%, 50 vol%, and 57 vol% of the total volume of solution A and solution B to prepare hybrid hydrogels with elastomer ratios of 8 vol%, 14 vol%, 40 vol%, 50 vol%, and 57 vol%.
[0040] Table 1 shows the adjustable range of the hybrid hydrogel with an elastomer ratio of 8-57 vol% in Example 1, including elastic modulus E (MPa), breaking strength σ f(MPa), elongation at break and toughness W (MJ / m 3 ).
[0041] Table 1 Adjustable range of mechanical properties of hybrid hydrogels with elastomer ratio of 8-57 vol%
[0042]
[0043] Example 2
[0044] The hybrid hydrogels were prepared by the following steps (the hydrogels with different elastomer crosslinker ratios were prepared in this example):
[0045] (1) 10 mg of photoinitiator 819, 0.36 mol% (relative to MA) of elastomer crosslinker 1,6-hexanediol dimethacrylate and 1 ml of elastomer monomer methyl acrylate were mixed uniformly to prepare solution A;
[0046] (2) 1 g of acrylamide and 2 mL of 1 vol% Tween 80 aqueous solution were manually shaken and mixed to obtain solution B;
[0047] (3) Solutions A and B were mixed together, vortexed for 5 min using a vortex disperser, and then injected into a glass mold with a 1 mm thick Teflon gasket using a syringe. After irradiation for more than 3 min, a hybrid hydrogel with an elastomer crosslinker usage of 0.36 mol% (relative to MA) was obtained.
[0048] According to the above preparation method, the usage amount of the elastomer crosslinking agent 1,6-hexanediol dimethacrylate is adjusted to 0 mol%, 0.09 mol%, 0.18 mol%, 0.72 mol%, 1.08 mol%, and 1.44 mol% (relative to MA) to prepare hybrid hydrogels with elastomer ratios of 0 mol%, 0.09 mol%, 0.18 mol%, 0.72 mol%, 1.08 mol%, and 1.44 mol%.
[0049] Table 2 shows the adjustable range of the hybrid hydrogel in Example 2 with an elastomer crosslinker ratio of 0-1.44 mol% (relative to MA), including elastic modulus E (MPa), breaking strength σ f (MPa), elongation at break and toughness W (MJ / m 3 ).
[0050] Table 2 Adjustable range of hybrid hydrogels with elastomer ratio of 0-1.44 mol% (relative to MA)
[0051]
[0052] Example 3
[0053] The hybrid hydrogels were prepared by the following steps (in this example, hydrogels with different hydrogel matrix cross-linking agent ratios were prepared):
[0054] (1) 10 mg of photoinitiator 819, 10 μl of 1,6-hexanediol dimethacrylate and 1 ml of elastomer monomer methyl acrylate were mixed evenly to prepare solution A;
[0055] (2) 1 g of acrylamide, 0.36 mol% (relative to AM) of a hydrogel matrix crosslinker N,N'-methylenebisacrylamide, and 2 mL of a 1 vol% Tween 80 aqueous solution were manually shaken and mixed to obtain solution B;
[0056] (3) Solutions A and B were mixed together, vortexed for 5 min using a vortex disperser, and then injected into a glass mold with a 1 mm thick Teflon gasket using a syringe. After irradiation for more than 3 min, a hybrid hydrogel with an elastomer crosslinker usage of 0.36 mol% (relative to MA) was obtained.
[0057] According to the above preparation method, the usage amount of the hydrogel matrix crosslinker was adjusted to 0 mol%, 0.045 mol%, 0.18 mol%, (relative to AM) to prepare hybrid hydrogels with hydrogel matrix crosslinker ratios of 0 mol%, 0.045 mol%, 0.18 mol%, etc.
[0058] Table 3 shows the adjustable range of the hybrid hydrogel with the usage of 0-0.36 mol% (relative to MA) of the hydrogel matrix crosslinker in Example 3, including elastic modulus E (MPa), breaking strength σ f (MPa), elongation at break and toughness W (MJ / m 3 ).
[0059] Table 3 Adjustable range of hybrid hydrogels with a usage of 0-0.36 mol% (relative to AM) of hydrogel matrix crosslinker
[0060]
[0061] Example 4
[0062] The hybrid hydrogels were prepared by the following steps (hydrogels with different agar contents were prepared in this example):
[0063] (1) 10 mg of photoinitiator 819, 10 μL of elastomer crosslinker 1,6-hexanediol dimethacrylate and 1 ml of elastomer monomer methyl acrylate were mixed to prepare solution A;
[0064] (2) 40 mg, 80 mg, 120 mg, 160 mg, and 200 mg of agar were respectively dissolved with 1 g of acrylamide and 2 mL of 1 vol% Tween80 aqueous solution at 90°C. Then, the mixture was vortexed and mixed evenly with solution A. The mixture was then injected into a mold and cooled at low temperature to form an agar first network. After irradiation for more than 3 minutes, a double network hybrid hydrogel with agar concentrations of 10 mg / ml, 20 mg / ml, 30 mg / ml, 40 mg / ml, and 50 mg / ml was obtained.
[0065] Table 4 shows the adjustable range of agar double network hybrid hydrogel with agar concentration of 10-50 mg / mL in Example 4, including elastic modulus E (MPa), breaking strength σ f (MPa), elongation at break and toughness W (MJ / m 3 ).
[0066] Table 4 Adjustable range of agar double network hybrid hydrogels with agar concentration of 10-50 mg / mL
[0067]
[0068] Example 5
[0069] The hybrid hydrogel (in this example, agar double network hydrogels with different elastomer crosslinkers were prepared) was prepared by the following steps:
[0070] (1) 10 mg of photoinitiator 819, 10 μL of elastomer crosslinker 1,6-hexanediol dimethacrylate and 1 ml of elastomer monomer methyl acrylate were mixed to prepare solution A;
[0071] (2) 120 mg agar, 1 g acrylamide and 2 mL 1 vol% Tween 80 aqueous solution were heated and dissolved at 90°C. Then, the mixture was vortexed and mixed evenly with solution A. Then, the mixture was injected into a mold and cooled at low temperature to form an agar first network. After irradiation for more than 3 minutes, an agar double network hybrid hydrogel was obtained.
[0072] According to the above preparation method, the usage amount of the elastomer crosslinking agent 1,6-hexanediol dimethacrylate was adjusted to 0.09 mol%, 0.18 mol%, 0.72 mol%, and 1.44 mol% relative to MA) to prepare agar double-network hybrid hydrogels with elastomer ratios of 0.09 mol%, 0.18 mol%, 0.72 mol%, and 1.44 mol%.
[0073] Table 5 shows the adjustable range of agar double network hybrid hydrogel in Example 5 with the usage of 0-1.44 mol% (relative to MA) of the elastomer crosslinker 1,6-hexanediol dimethacrylate, including elastic modulus E (MPa), breaking strength σ f(MPa), elongation at break and toughness W (MJ / m 3 ).
[0074] Table 5 Adjustable range of agar double network hybrid hydrogels with elastomer crosslinker usage of 0.09-1.44 mol% (relative to MA)
[0075]
[0076] In summary, the present invention is an emulsion mixed with a free radical polymerization initiator, an oil-soluble elastomer monomer and an elastomer crosslinker, a water-soluble hydrogel matrix monomer and a water-soluble hydrogel matrix crosslinker, and a surfactant, water, etc., which is copolymerized in one step by light / heat to form a network of elastomer and hydrogel at the same time, and a strong interface is formed between the two phases through covalent bonds, thereby synthesizing an elastomer hybrid hydrogel. The method is simple and easy to operate. Easy to form: It can be transferred to a mold with a suitable structure as needed to directly prepare a hydrogel shape with complex three-dimensional shapes and accurate details.
[0077] As attached Figure 1-7 As shown in the data of Tables 1-5, the hydrogel of the present invention has good controllability, and its performance can be significantly changed by slight component adjustments. For example, compared with the control sample, the mechanical properties are greatly improved by adding an elastomer, and continue to become stronger as the proportion of the elastomer increases. The present invention can adjust the raw material components and the ratio between them according to the specific application scenario to prepare hydrogel materials with different mechanical properties, intelligent responsiveness, and transparency, and has good application prospects in the fields of biomedicine, sensors, soft robots, etc.
[0078] The specification and drawings of the present invention are considered to be illustrative rather than restrictive. On the basis of the present invention, those skilled in the art can make some substitutions and modifications to some of the technical features according to the disclosed technical content without creative labor, all of which are within the protection scope of the present invention.
Claims
1. A tough elastic hybrid hydrogel, characterized in that: The invention comprises the following raw material components: an initiator, an elastomer monomer, an elastomer crosslinking agent, a water-soluble monomer, a water-soluble crosslinking agent, a surfactant and water; the elastomer monomer accounts for 1-90% of the total volume of the raw material components, the elastomer crosslinking agent accounts for 0-100 mol % of the elastomer monomer, and the water-soluble crosslinking agent accounts for 0-20 mol % of the water-soluble monomer.
2. A tough elastic hybrid hydrogel according to claim 1, characterized in that: The initiator is 0.01-1 mol% of the elastomer monomer; the ratio of the mass of the water-soluble monomer to the volume of water is 1:2; the volume ratio of the elastomer monomer to water is 0.25-4:2; and the volume ratio of the surfactant to water is 0.05-0.1:
1.
3. A tough elastic hybrid hydrogel according to claim 1, characterized in that: The raw material components also include agar, and the concentration of agar in the raw material components is 10-50 mg / mL.
4. A tough elastic hybrid hydrogel according to claim 1, characterized in that: The initiator is a free radical polymerization thermal initiator or a photoinitiator; the thermal initiator is one of dibenzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), potassium persulfate (KPS), and ammonium persulfate (APS); the photoinitiator is one of 1-hydroxycyclohexyl phenyl ketone, phenyl dimethoxyacetophenone, photoinitiator 2959, A-ketoglutaric acid, photoinitiator LAP, photoinitiator 819, photoinitiator TPO, and benzophenone (BP).
5. The tough elastic hybrid hydrogel according to claim 1, characterized in that: The elastomer monomer is one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-phenylethyl acrylate, isooctyl methacrylate, n-octyl acrylate, isooctyl acrylate, diethylaminoethyl methacrylate, vinyl propionate, methyl methacrylate, butyl methacrylate, hexyl methacrylate, and vinyl acetate.
6. The tough elastic hybrid hydrogel according to claim 1, characterized in that: The elastomer crosslinking agent is one of ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,12-dodecanediol dimethacrylate, 1,13-tridecanediol dimethacrylate, p-vinylbenzene and spiropyran.
7. The tough elastic hybrid hydrogel according to claim 1, characterized in that: The water-soluble monomer is one of acrylamide, methacrylamide, N-(2-hydroxyethyl)acrylamide, N,N-dimethylacrylamide, N-acryloylglycinamide, acrylic acid, N-isopropylacrylamide, and hydroxyethyl methacrylate; the water-soluble crosslinking agent is one of N,N'-methylenebisacrylamide, polyethylene glycol 600 diacrylate, and polyethylene glycol 1000 diacrylate.
8. The tough elastic hybrid hydrogel according to claim 1, characterized in that: The surfactant is one of Tween 20, Tween 60, Tween 80, PVP, Span, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.
9. A method for preparing a tough elastic hybrid hydrogel as claimed in claim 1, characterized in that: The following steps are involved: S1, mixing an initiator, an elastomer crosslinking agent and an elastomer monomer uniformly to prepare a solution A; S2, uniformly mixing a water-soluble monomer, a water-soluble crosslinking agent and an aqueous solution containing a surfactant to obtain a solution B; S3. Evenly mix solution A in S1 and solution B in S2 at a volume ratio of 0-1.3:1, inject into a mold, initiate polymerization, and obtain a strong elastomer hybrid hydrogel.
10. A tough elastic hybrid hydrogel according to any one of claims 1 to 8, characterized in that: The tensile strength of the hydrogel is 0.1MPa-3.3MPa; the elongation at break is 3.2-22.5; and the elastic modulus is 0.2MPa-1.9MPa.
Citation Information
Patent Citations
Preparation method of high-strength hydrogel
CN103739861A
Preparation method of ionic / chemical hybrid bi-crosslinked polyacrylic high strength hydrogel
CN106832345A
Hydrogel capsule and method for producing the same
JP2012011269A
High-strength gel
JP2015096560A
Nanocomposite ion exchange hydrogels
US20110098369A1